Persea quarciticola (Lauraceae), a new species from Espírito Santo, Brazil - de Moraes, Pedro Luís Rodrigues [UNESP]; Brotto, Marcelo Leandro (Springer Nature, 2024)
Persea is a genus of Lauraceae with about 101 accepted species from the Americas and another two from the Macaronesian Islands and the Azores. The New World species occur in subtropical to tropical regions from sea level to ca. 4000 m. Recent field work in southeastern Brazil, as well as the study of 1432 collections of Brazilian Persea, revealed a new species that we describe here as Persea quarciticola. The new species belongs to Persea subg. Eriodaphne. It is restricted to the ‘morros de sal’ (mountains of quartz) of Vargem Alta, Espírito Santo, between 600 and 800 m. We provide a complete description of the new species, including illustrations, a distribution map, and discussion on its putative relationships within the genus.
Keywords: Atlantic Rain Forest; biodiversity; Eriodaphne; Neotropics; plant taxonomy